Patients' experiences of psychiatric care in emergency departments: A secondary analysis. (May 2016) - Harris, Barbara; Beurmann, Ross; Fagien, Samantha; Shattell, Mona M.
Highlights: RN should moderate stimuli in the ED to prevent added distress. Mental health patients may perceive time pressure as lack of caring. Person-centered care enables mental health patients to participate in care. Symptoms of mental illness may make it difficult to adhere to ED procedures. Abstract: The number of psychiatric emergencies presenting to EDs in the United States continues to rise. Evidence suggests that psychiatric ED care encounters can have less than optimal outcomes, and result in stress for providers. The primary aim of this study is to describe the perceptions of ED visits by persons experiencing emotional distress, identifying themes among these that may guide nursing interventions that minimize stress and optimize outcomes in the treatment of psychiatric emergency. This secondary analysis used a qualitative, phenomenological method to analyze a de-identified data set originally collected in a study of experiences of psychiatric emergency in a community based crisis management setting. Findings consist of three major themes: "Emergency rooms are cold and clinical", "They talk to you like you're a crazy person", and "You get put away against your will". An overarching theme through all three is the influence of RN communication, both positive and negative, on patient perceptions of their ED encounters. While nurse–patient communication is basic to all areas of practice, it may be a low priority in the urgent and chaotic context of the ED. However, our findings suggest that increased attention to timely, empathic and validating communication and openness to the patient's reality may decrease severity of symptoms, optimize outcomes, and decrease provider stress.